2020
DOI: 10.1177/2158244020902085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Research Performance of Islamabad-Based Higher Education Institutes

Abstract: Research discovers new knowledge, ideas, and technologies essential in driving the future of society and humanity. Without research, a relevant and modern country cannot exist. Similarly, the research output of universities and degree-awarding institutes (DAIs) plays a significant role in higher education and development of any country. Research fosters professional excellence in faculty, important for delivering outstanding student education and training. Therefore, this research is an evaluation of the resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In this regard, any organisational change would be more positive for Impact of Servant Leadership on Follower Turnover Intentions: Mediating Role of Resilience the followers. With a desire for a better regional and global university ranking, Pakistan has started to reform its higher education system since 2002 (Javed, Ahmad, & Khahro, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, any organisational change would be more positive for Impact of Servant Leadership on Follower Turnover Intentions: Mediating Role of Resilience the followers. With a desire for a better regional and global university ranking, Pakistan has started to reform its higher education system since 2002 (Javed, Ahmad, & Khahro, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among the others, research performance has the most considerable portion in the higher education performance evaluation (Javed et al, 2020;Bonaccorsi & Secondi, 2017;Frenken et al, 2017) both nationally (DIKTI Kemendikbud) and internationally (Times Higher Education, Shanghai Ranking, QS World Ranking, Webometrics, etc.). For instance, Times Higher Education (THE) rated research and citation performance as more than 60% of the total assessment (Times Higher Education, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research is essential in producing integrative science (Husni, 2017). Thus, PTBP institutions needed to improve their research performance to improve overall institutional performance and ultimately increase competitiveness (Javed et al, 2020;Artés et al, 2017;Edgar & Geare, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesantren-based Higher Education (PTBP) integrated both higher education and pesantren education systems (Zarkasyi, 2017) to respond to global challenges (Thoyib et al, 2020;Tohet & Eko, 2020;Bali, 2017) and is alleged as an ideal Islamic higher education model considering its critical role in the process of integration-interconnection of science and Islamic teaching (Tohet & Eko, 2020;Husni, 2017;Halil & Anwar, 2016).However, despite many Muslim scholars claimed PTBP as an ideal Islamic higher education, the fact showed that PTBP inability to compete with other higher education is undeniable. Thus, PTBP institutions needed to improve their organizational performance to increase competitiveness and ultimately depend on lecturers' performance (Javed et al, 2020;Artés et al, 2017;Edgar & Geare, 2013). Lecturers are the most important human resource in higher education (Javed et al, 2020;Mashudi, 2020).…”
Section: Introductionmentioning
confidence: 99%